Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
- 81
Step-by-step explanation:
- (x + y)⁴ =
- ((x + y)²)² =
- (x² + y² + 2xy)² =
- (5 + 2*2)² =
- 9² =
- 81
The given information is,
- x² + y² = 5
- xy = 2
[tex] \sf \: The \: solution \: of \: (b) \: will \: be, \\ \sf → (x + y)^4 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \sf → ((x + y)²)² \: \: \: \: \: \: \: \: \: \: \: \\ \sf → (x² + y² + 2xy)² \: \\ \sf → {5 + (2 × 2)}² \: \: \: \: \: \: \: \: \: \\ \sf \to (5 + 4)² \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ → \sf 9² = 81 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: [/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.